Effectiveness of One-Stop Administrative Services for the Community - Rifai Ahmad; Firmansyah; Adilansyah (Program Studi Administrasi Negara Universitas Serang Raya, 2022)
Administrative services that often occur are considered low quality due to lack of human resources, unclear time certainty and inadequate infrastructure, thus giving a bad assessment from the community. This is the background behind the formation of the Minister of Home Affairs Regulation No. 24 of 2006 regarding PTSP (One Stop Integrated Implementation Guidelines) to improve the quality of public services to the community organized by the government. However, the implementation of PTSP has yet to be implemented in all Indonesian government institutions because several institutions still have difficulties and doubts about its effectiveness. This is the author's background to discuss the Effectiveness of One Stop Administration Services for the Community. This study aims to determine whether there is effectiveness and the level or value of effectiveness provided in providing administrative services for the community through a one-stop line or system in City Y. The method used is descriptive quantitative with data collection techniques, namely observation and interview documentation. Moreover, the distribution of the questionnaire to 100 respondents who were selected by purposive sampling. The study results show that the one-stop administrative service is quite effective at 30%. However, it is insignificant in its effectiveness because it still requires adaptation to the system and improvements in various ways.